The presence and predictors of complicated grief symptoms in perinatally bereaved mothers from a bereavement support organization - McSpedden, M.; Mullan, Barbara; Sharpe, L.; Breen, Lauren; Lobb, E. (Routledge, 2017)
The present study investigated the presence and possible predictors of complicated grief symptoms in perinatally bereaved mothers (N = 121) up to 5 years postbereavement. The presence of complicated grief scores in the clinical range was 12.4%, which is higher than in many other bereaved populations, and the presence of other living children may protect against the development of complicated grief symptoms. The majority of the women were able to negotiate a perinatal loss without developing complicated grief; however, there remains an important group of women who up to 5 years later score in the clinical range for complicated grief symptoms.